2022
DOI: 10.3389/fonc.2022.896795
|View full text |Cite|
|
Sign up to set email alerts
|

A Comparison Study Between CNN-Based Deformed Planning CT and CycleGAN-Based Synthetic CT Methods for Improving iCBCT Image Quality

Abstract: PurposeThe aim of this study is to compare two methods for improving the image quality of the Varian Halcyon cone-beam CT (iCBCT) system through the deformed planning CT (dpCT) based on the convolutional neural network (CNN) and the synthetic CT (sCT) generation based on the cycle-consistent generative adversarial network (CycleGAN).MethodsA total of 190 paired pelvic CT and iCBCT image datasets were included in the study, out of which 150 were used for model training and the remaining 40 were used for model t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…The dpCT images were deformed from the pCT images to the CBCT images, and the sCT images were generated based on CBCT images, both of which had similar anatomical structures to the CBCT images, especially the high geometric similarity of the skin and bony structures. As we found in our previous work [27], the DIR method appeared to be ineffective for large deformable structures composed of soft tissue, and sCT might produce some arti cial structures inconsistent with the CBCT images, which caused the slight difference in the anatomical structures of the dpCT images and sCT images. In Fig.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The dpCT images were deformed from the pCT images to the CBCT images, and the sCT images were generated based on CBCT images, both of which had similar anatomical structures to the CBCT images, especially the high geometric similarity of the skin and bony structures. As we found in our previous work [27], the DIR method appeared to be ineffective for large deformable structures composed of soft tissue, and sCT might produce some arti cial structures inconsistent with the CBCT images, which caused the slight difference in the anatomical structures of the dpCT images and sCT images. In Fig.…”
Section: Discussionmentioning
confidence: 65%
“…The methods underlying the development of the DIR network and sCT generation network are described in detail in our previous work [27]. Brie y, the DIR network is based on a 3D multistage registration network (MSnet), which includes three stages of registration, each of which consists of two downsampling…”
Section: Deformable Image Registration and Sct Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Various research groups have described linear normalization 11,[18][19][20][21][22][23] and nonlinear normalization preprocessing methods using the hyperbolic tangent function (Tanh), 24,25 where Tanh(x) = e x −e −x e x +e −x . With reference to the above literature, 11,[18][19][20][21][22][23][24][25] we defined two linear normalization and one nonlinear normalization preprocessing methods employed in this work as follows:…”
Section: Different Normalization Preprocessing Methodsmentioning
confidence: 99%
“…A trained GA-B could generate image A’, which has the structure of image A and the style of image B. CycleGAN models ( 24 ) include two generators and two discriminators and add cycle-consistency loss for training. CycleGAN has been widely used for interconversion between different types of medical images ( 25 30 ). The structure of CycleGAN used in this study is consistent with that reported in the literature ( 24 ), and the model structure is shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%